2019
DOI: 10.3892/ol.2019.10710
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MAGT1 is associated with aggressiveness and poor prognosis of colorectal cancer

Abstract: Tumor metastasis and anticancer drug resistance are the major causes of mortality in patients with colorectal cancer (CRC). Due to the limitations of conventional biomarkers, it is urgent to identify novel and valid biomarkers to predict the progression and prognosis of CRC. Reverse transcription-quantitative polymerase chain reaction and western blotting were used to detect MAGT1 expression in CRC clinical samples or cell lines. Bioinformatics analysis was used to investigate the association between MAGT1 alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Subsequently, we found that miR-628-5p could bind to the 3ʹUTR of MAGT1, which was closely associated with human cancer progression. 16,17 We next measured the level of MAGT1 and found was highly expressed in glioma tissues and cells, whereas its level was conspicuously downregulated in glioma cells treated with Sev. Besides, circ_0002755 modulated MAGT1 expression via interacting with miR-628-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we found that miR-628-5p could bind to the 3ʹUTR of MAGT1, which was closely associated with human cancer progression. 16,17 We next measured the level of MAGT1 and found was highly expressed in glioma tissues and cells, whereas its level was conspicuously downregulated in glioma cells treated with Sev. Besides, circ_0002755 modulated MAGT1 expression via interacting with miR-628-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al reported that overexpression of MAGT1 led to the poor prognosis of colorectal cancer. 16 Wang et al found that microRNA-199a-5p inhibited glioma progression by inhibiting MAGT1. 17 Therefore, MAGT1 might be an attracting drug target for glioma and its function in Sev-mediated glioma progression should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…TRPM7 expression was also associated with tumor infiltration, tumor grade, and the presence of distant metastasis [ 81 , 82 ]. In qRT-PCR-based and in silico studies, the Mg 2+ transporter MAGT1 was found to be overexpressed in colorectal cancerous tissues [ 83 ]. High MAGT1 expression also correlates with chemotherapeutic resistance, metastatic status, and tumor stage [ 83 ].…”
Section: Expression Of Mg 2+ Transporters In DImentioning
confidence: 99%
“…In qRT-PCR-based and in silico studies, the Mg 2+ transporter MAGT1 was found to be overexpressed in colorectal cancerous tissues [ 83 ]. High MAGT1 expression also correlates with chemotherapeutic resistance, metastatic status, and tumor stage [ 83 ]. CNNM4 protein was also found downregulated in an IHC analysis of cancerous colorectal tissues, and inversely correlates with tumor malignancy [ 84 ].…”
Section: Expression Of Mg 2+ Transporters In DImentioning
confidence: 99%
“…And the evolutionary rate of MAGT1 (magnesium transporter 1) was 0.33127 in extremely large carnivores, 6.1 times of that in background group. Loss of MAGT1 would disrupt T cell signaling and lead to a novel human primary immunode ciency [55], and furthermore, overexpression of MAGT1 was associated with development and metastasis of colorectal cancer [56]. Here, we obtained 100 cancer-related genes that were signi cantly associated with body size evolution in carnivores including 15 cancer-related REGs that identi ed in extremely large group, which might protect them from cancer invasion, special for large and long-lived species.…”
Section: Molecular Evidence For the Peto's Paradox In Carnivores?mentioning
confidence: 99%